О пондеромоторных силах, действующих на стенки прямоугольного волновода при несогласованной нагрузке - Орлов, В.Г.; Кукуш, В.Д. (Radiotekhnika, 1966)
О пондеромоторных силах, действующих на стенки прямоугольного волновода при несогласованной нагрузке